Design Product Parameters for Customer Needs on Mineral Water Packaging from The Prespective of A Product Design - Jakaria, Ribangun bamban; Iswanto, Iswanto; Arifin, Nur Haizal binti Mat Yaakop (Journal of Research and Technology, 2024)
Suli Mineral Water is a bottled drinking water product founded by the Muhammadiyah Regional Leadership Economic and Entrepreneurship Council (MEK-PDM) Tuban, East Java in establishing the Suli 5 Bottled Drinking Water company which is a franchise of PT. Suryatama Cemerlang Abadi (SCA) as Suli's holding company 5. The use of Suli drinking water in all business charities has not yet shown a positive trend. This problem is important to research because drinking water supplies have the potential to grow and develop. This research aims to identify consumer preferences for drinking water packaging product design as a recommendation for marketing and manufacturing policies. The research method used is the traditional conjoint method which is used to measure the utility value and relative importance of each bottled water product design attribute to determine consumer preferences for these attributes. The data collection process in this research was carried out in December 2023 - March 2024. The sample chosen was a non-probability sampling, namely using a judgment sampling technique with a total of 200 respondents. The results of this research are that product parameters consist of product performance, features, reliability, suitability, durability, service capability, quality impression (perception), aesthetics, and product packaging so that using combined analysis provides quantitative information so that modeling of consumer preferences in producing combination of features in the 600 ml suli packaging product design